Pengaruh Return On Asset (ROA) Terhadap Nilai Perusahaan Subsektor Food and Beverage di Bursa Efek Indonesia Periode 2016-2018 - Masayu Soraya Humairah; Fetty Maretha; Marieska Lupikawaty (Jurnal Terapan Ilmu Ekonomi, Manajemen dan Bisnis, 2021)
This study aims to analyze the effect of Return On Assets (ROA) on Firm Value in the Indonesia Stock Exchange. Sampling in this study using purposive sampling method. This study uses secondary data in the form of annual reports obtained from the Indonesia Stock Exchange. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that partially Return on Assets (ROA) has a significant effect on Firm Value (PBV). The size of the Return on assets (ROA) can have an increasing effect on Firm Value, meaning that the higher the financial performance as measured by Return on Assets (ROA), the better the productivity of assets in obtaining net profit